2018
DOI: 10.1177/0022034518797274
|View full text |Cite
|
Sign up to set email alerts
|

American Association for Dental Research Policy Statement on Community Water Fluoridation

Abstract: See Acknowledgments for the full list of committee members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Under current Queensland government legislation, the decision to implement CWF rests with local authorities with many opting out since the legislation changed. Following on recent research developments and persistent challenges to CWF, the AADR published a policy statement which supports its safety and efficacy . It similarly continues to be endorsed and supported by the Australian NHMRC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under current Queensland government legislation, the decision to implement CWF rests with local authorities with many opting out since the legislation changed. Following on recent research developments and persistent challenges to CWF, the AADR published a policy statement which supports its safety and efficacy . It similarly continues to be endorsed and supported by the Australian NHMRC .…”
Section: Discussionmentioning
confidence: 99%
“…Community Water Fluoridation is widely regarded as a safe and effective evidence‐based intervention for the prevention of dental caries, as confirmed recently by a 2018 American Association for Dental Research (AADR) policy statement . The Australian National Health and Medical Research Council (NHMRC) Information Paper on Water Fluoridation (2017) stated that CWF reduced tooth decay by between 26% and 44% in children, teenagers and adults .…”
Section: Introductionmentioning
confidence: 99%
“…Dental Research (AADR) recommend conventional fluoride dentifrices restricting the amount of fluoride according to age: smear size amount for children younger than two years old and pea-sized amount for children between ages two to five years old [10,11]. The guidelines also recommend adult supervision while children brush their teeth.…”
Section: The Current Guidelines Of American Academy Of Pediatric Dentmentioning
confidence: 99%
“…For example, the issue of community water fluoridation for the prevention of dental caries has been the subject of intense debate over many years. The scientific evidence generally points to reductions in dental caries in fluoridated areas, and community water fluoridation is supported by the International and American Associations for Dental Research (Ajiboye 2018; IADR 1999, 2018; Schluter et al 2020). Nevertheless, an analysis of Twitter between 2009 and 2017 found that at least 59.2% of tweets on the topic of water fluoridation expressed negative opinions and less than 15% of tweet mentions were positive (Oh et al 2020).…”
mentioning
confidence: 99%